Harnessing diesel-degrading potential of an antarctic microalga from greenwich island and its physiological adaptation - Lim, Zheng Syuen; Wong, Chiew-Yen; Ahmad, Siti Aqlima; Puasa, Nurul Aini; Phang, Lai Yee; Shaharuddin, Noor Azmi; Merican, Faradina; Convey, Peter; Zulkharnain, Azham; Shaari, Hasrizal; Azmi, Alyza Azzura; Kok, Yih-Yih; et al. (Multidisciplinary Digital Publishing Institute, 2023)
Microalgae are well known for their metal sorption capacities, but their potential in the remediation of hydrophobic organic compounds has received little attention in polar regions. We evaluated in the laboratory the ability of an Antarctic microalga to remediate diesel hydrocarbons and also investigated physiological changes consequent upon diesel exposure. Using a polyphasic taxonomic approach, the microalgal isolate, WCY_AQ5_1, originally sampled from Greenwich Island (South Shetland Islands, maritime Antarctica) was identified as Tritostichococcus sp. (OQ225631), a recently erected lineage within the redefined Stichococcus clade. Over a nine-day experimental incubation, 57.6% of diesel (~3.47 g/L) was removed via biosorption and biodegradation, demonstrating the strain’s potential for phytoremediation. Fourier transform infrared spectroscopy confirmed the adsorption of oil in accordance with its hydrophobic characteristics. Overall, degradation predominated over sorption of diesel. Chromatographic analysis confirmed that the strain efficiently metabolised medium-chain length n-alkanes (C-7 to C-21), particularly n-heneicosane. Mixotrophic cultivation using diesel as the organic carbon source under a constant light regime altered the car/chl-a ratio and triggered vacuolar activities. A small number of intracellular lipid droplets were observed on the seventh day of cultivation in transmission electron microscopic imaging. This is the first confirmation of diesel remediation ability in an Antarctic green microalga.